2010
DOI: 10.1088/0004-637x/716/2/1269
|View full text |Cite
|
Sign up to set email alerts
|

Angular Momentum Transport in Solar-Type Stars: Testing the Timescale for Core-Envelope Coupling

Abstract: We critically examine the constraints on internal angular momentum transport which can be inferred from the spin down of open cluster stars. The rotation distribution inferred from rotation velocities and periods are consistent for larger and more recent samples, but smaller samples of rotation periods appear biased relative to v sin i studies. We therefore focus on whether the rotation period distributions observed in star forming regions can be evolved into the observed ones in the Pleiades, NGC 2516, M 34, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
185
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(198 citation statements)
references
References 56 publications
13
185
0
Order By: Relevance
“…Using a diffusive approach, Eggenberger et al (2012b) showed that an enhanced "anomalous" viscosity of ν = 3 × 10 4 cm 2 s −1 is required to account for the rotational splitting of the red giant KIC 8366239, whose rotational profile is much shallower than diffusive models would predict. Using the conversion we derived above from Denissenkov et al (2010), this translates into a coupling timescale of 78 Myr, i.e. not very different than the one we derived from our PMS-MS models.…”
Section: Core-envelope Decoupling and The Timescale For Angular Momenmentioning
confidence: 54%
See 3 more Smart Citations
“…Using a diffusive approach, Eggenberger et al (2012b) showed that an enhanced "anomalous" viscosity of ν = 3 × 10 4 cm 2 s −1 is required to account for the rotational splitting of the red giant KIC 8366239, whose rotational profile is much shallower than diffusive models would predict. Using the conversion we derived above from Denissenkov et al (2010), this translates into a coupling timescale of 78 Myr, i.e. not very different than the one we derived from our PMS-MS models.…”
Section: Core-envelope Decoupling and The Timescale For Angular Momenmentioning
confidence: 54%
“…These new observational results provide extremely useful guidance for the modelling of angular momentum evolution of low-mass stars (M * < 1.2 M ) from 1 Myr to 10 Gyr (e.g. Irwin et al 2007;Bouvier 2008;Denissenkov et al 2010;Spada et al 2011;Reiners & Mohanty 2012;Gallet & Bouvier 2013) and offer a unique insight into the physical processes that dictate rotational evolution. To account for the observations, parametric models have to incorporate at least three major processes: the star-disk interaction during the early pre-main sequence (PMS; Matt & Pudritz 2005b;Zanni & Ferreira 2009Ferreira et al 2000;Matt et al 2010), the loss of angular momentum through powerful stellar winds on the early main sequence (MS; Weber & Davis 1967;Kawaler 1988;Matt & Pudritz 2005a;Vidotto et al 2011Vidotto et al , 2014bZanni & Ferreira 2011;Cranmer & Saar 2011;Matt et al 2012a,b;Reiners & Mohanty 2012;Réville et al 2015), and the redistribution of angular momentum in the stellar interior at all phases of evolution (MacGregor & Brenner 1991;Allain 1998;Palacios et al 2003Palacios et al , 2006Charbonnel & Lagarde 2010;Lagarde et al 2011Lagarde et al , 2012Charbonnel et al 2013).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The first important observational fact in this context is that the rotational periods of young solar-type stars suggest that slow rotators develop a high degree of differential rotation between the radiative core and the convective envelope, while solid-body rotation is favoured for fast rotators (see e.g. Irwin et al 2007;Bouvier 2008;Denissenkov et al 2010). The rotation of the star on the ZAMS basically depends on its initial velocity and on the disc lifetime during the pre-main sequence.…”
Section: Introductionmentioning
confidence: 99%